Measuring workers' financial incentives - Daniel Bias; Lin Chen; Benjamin Lochner; Thomas Schmid (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2020)
We propose a novel measure for workers' financial incentives based on withinestablishment wage differences among similar workers from the same occupation. This measure captures all forms of incentive pay that lead to workeremployer-specific pay premiums, including explicit (e.g., bonuses) and implicit forms (e.g., tournaments). We estimate the measure using a linked workerestablishment-firm dataset that covers 31 million workers in Germany. For validation, we exploit survey-based information on performance pay and variation in monitoring costs due to occupational characteristics, establishment size, and task complexity and show that the measure behaves as theoretically predicted. Applying the measure yields evidence that workers' incentives positively correlate with firms' performance and innovativeness, which supports a positive relationship between incentives and effort.
Keywords: 330